2020
DOI: 10.3390/land9030076
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Linkages among Mining Production and Land Rehabilitation Efficiency in China

Abstract: In the context of China's economic transformation, the consumption of mineral resources plays an important role in its economy's sustainable development, and so improving mining efficiency is regarded as the basis of industrial development. However, in the pursuit of mine exploitation, the destruction of land resources has attracted greater attention by government and society, with many scholars focusing more on land rehabilitation in recent years. Thus, from the perspective of climate change, this research sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…These are, in conclusion, good for the territory. Recovering and reconverting a former extractive hypogeal site means to recognise the opportunities and, at the same time, the limits offered by the quarries, and the nature and characteristics of the excavated material [18]. The regenerative force exercisable by these marginal voids is becoming the strong point of the so-called "new ecologies", which utilises the existent heritage at the centre of the project for the contemporary city.…”
Section: The New Value Of the Industrial Landscapementioning
confidence: 99%
“…These are, in conclusion, good for the territory. Recovering and reconverting a former extractive hypogeal site means to recognise the opportunities and, at the same time, the limits offered by the quarries, and the nature and characteristics of the excavated material [18]. The regenerative force exercisable by these marginal voids is becoming the strong point of the so-called "new ecologies", which utilises the existent heritage at the centre of the project for the contemporary city.…”
Section: The New Value Of the Industrial Landscapementioning
confidence: 99%
“…Concurrently, this efficiency boost can drive technological advancements, thereby reducing the carbon footprint of the plantation industry. Given the challenge of identifying an apt instrumental variable at the macro scale, we employed the lagged variable from a prior period of agricultural technical efficiency as a proxy, thereby addressing potential endogeneity concerns [ 37 ]. Table 6 displays the test outcomes.…”
Section: Empirical Results and Analysismentioning
confidence: 99%
“…Cai et al introduced a propensity score matching method to analyze the average treatment effect of the effect of participation in land transfer on the technical efficiency of transferring and nontransferring farmers, further confirming that land transfer does increase technical efficiency after matching factors such as age, gender, education level, farming experience, and the number of family members working in agriculture [2]. Shi found that land transfer improves the technical efficiency of agricultural production by correcting labor mismatch, while it has a limited effect on correcting land mismatch status, further explaining the mechanism by which land transfer affects the technical efficiency of agricultural production [3].…”
Section: Agricultural Production Efficiency Effects Of Land Transfermentioning
confidence: 90%